The Fragile Balance of Terror Deterrence in the New Nuclear Age - Narang, Vipin; Sagan, Scott D. (Cornell Studies in Security Affairs, 2023)
In The Fragile Balance of Terror, the foremost experts on nuclear policy and strategy offer insight into an era rife with more nuclear powers. Some of these new powers suffer domestic instability, others are led by pathological personalist dictators, and many are situated in highly unstable regions of the world-a volatile mix of variables. The increasing fragility of deterrence in the twenty-first century is created by a confluence of forces: military technologies that create vulnerable arsenals, a novel information ecosystem that rapidly transmits both information and misinformation, nuclear rivalries that include three or more nuclear powers, and dictatorial decision making that encourages rash choices. The nuclear threats posed by India, Pakistan, Iran, and North Korea are thus fraught with danger. The Fragile Balance of Terror, edited by Vipin Narang and Scott D. Sagan, brings together a diverse collection of rigorous and creative scholars who analyze how the nuclear landscape is changing for the worse. Scholars, pundits, and policymakers who think that the spread of nuclear weapons can create stable forms of nuclear deterrence in the future will be forced to think again. Contributors: Giles David Arceneaux, Mark S. Bell, Christopher Clary, Peter D. Feaver, Jeffrey Lewis, Rose McDermott, Nicholas L. Miller, Vipin Narang, Ankit Panda, Scott D. Sagan, Caitlin Talmadge, Heather Williams, Amy Zegart